Unique reproductive biology of the broadcasting sea cucumber Holothuria floridana: facultative recruitment on adults inside nursery grounds. Issue 2 (3rd April 2021) - Rogers, Arlenie; Hamel, Jean-François; Quetzal, Junior; Mercier, Annie
ABSTRACT: Information on newly settled juveniles and recruitment processes in sea cucumbers is sparse for most commercial species, impeding protection of nursery habitats, which are key to management. Here, the ecology of early life stages of Holothuria floridana was investigated. In laboratory experiments, females released a small number of oocytes, which underwent abbreviated lecithotrophic development. During broadcast spawning, some of the negatively buoyant and sticky oocytes settled on the adults where they remained anchored up to the pentactula stage (encapsulated). Several wild adults collected in the Placencia Lagoon (Belize) each hosted ~2 propagules (eggs, blastulae, pentactulae, juveniles). The nursery habitat was characterized by high adult density, shallow seagrass beds close to mangroves, and mud dominated substrata. The present work illustrates a unique facultative offspring-adult association in a free-spawning lecithotrophic species of Holothuroidea, possibly representing a hybrid state between broadcasting and external brooding. This uncommon reproductive feature may ensure successful local recruitment in one of the most competitive habitats of the tropical Americas, where predation pressure is likely to be very high.